The radiological diagnosis of pregnancy associated venous thromboembolism: a review of current research - Yang, Di; Wang, Li (Frontiers in Medicine, 2024)
One of the main causes of unfavorable pregnancy outcomes in expectant mothers is pregnancyassociated venous thromboembolism. Although pregnancy-related venous thromboembolism does not always manifest obvious clinical symptoms and lacks a comprehensive standard risk assessment and prediction system as well as simple and effective laboratory testing techniques, timely and accurate diagnosis can still help reduce the probability of adverse pregnancy outcomes. To aid in the early detection, diagnosis, and treatment of pregnancy-associated venous thromboembolism, we attempt to provide an overview of the radiological diagnostic techniques for various forms of the condition.